Analisis Yuridis Keabsahan Perjanjian Pinjaman Online Fintech Dalam Upaya Mengurangi Resiko Pinjaman Online - Yudi Nurul Anwar (Sanskara Hukum dan HAM, 2022)
Various the coviience provided in using credit online does not include immediately provide benefits to the debtor. Determination of interest rates does not havea clear reference often incurs interest expense with an amount of large to the debtor. For this reason, it is interesting to do more research more about the validity of online credit agreements from the perspective of The Civil Code ad effort to reduce the rik of online loans. The research carried out I ormative legal research with the following materials, primary law which cosist of laws and all regulations related to object tudy. Ecodary legal material and tertiary legal materials in the form of books law, legal dictionaries relevant to the topic in this study. Based on the results of the esearch conducted, it can e understood that credit agreements made online from the perspective of the Civil Code is a valid agreement because it fulfill and does not conflict with the legal elements of an agreement contained in Pasal 132 Civil Code. Legal protection provided in the credit agreement online basically refer to Pasal 1365 of The Civil Code regarding acts against the law. Administrative sanctions are also applied as an effort legal protection for ay fitech that does not register with OJK.